The Impact of Gadget Use on Mental Health and Student Motivation to Learn at School - Abdulloh Aziz Assa'diy; Tiara Azizah Maharani; May Yasir Maulana (Institut Studi Islam Muhammadiyah Pacitan, 2025)
The development of digital technology has brought significant changes to the world of education; however, uncontrolled gadget use poses serious problems for students' mental health and learning motivation. This study is crucial for understanding the complex relationship between digital technology and adolescent well-being to develop effective and sustainable intervention strategies. The primary objective of this article is to deeply and comprehensively analyze the impact of gadget use on the mental health and learning motivation of students through a systematic literature review. The method employed is qualitative with a literature review approach, synthesizing data from various scientific databases published between 2014 and 2024. The results indicate that excessive gadget use triggers emotional disorders, depression, anxiety, and sleep disturbances that damage cognitive functions. Mental health was found to act as a mediating variable that directly contributes to the decline of intrinsic motivation and academic engagement. This article contributes a holistic approach integrating psychological and pedagogical aspects, while offering practical, measurable recommendations for educators and parents to mitigate the negative impacts of technology in the school environment.